2020
DOI: 10.1021/jacs.0c05726
|View full text |Cite|
|
Sign up to set email alerts
|

Silver-Catalyzed Enantioselective Propargylic C–H Bond Amination through Rational Ligand Design

Abstract: reaction mixture was diluted with E2O and washed with H2O. The aqueous layer was extracted with E2O three times. The combined organic layer was washed with H2O (three times) and brine, dried over Na2SO4, filtered, and concentrated under reduced pressure. The crude material was purified by silica gel column chromatography (0→70% EtOAc/hexanes) to afford the desired trifluoromethylated alkyne S5 as a white solid (0.26 g, 44% yield); 1 H NMR (500 MHz, CDCl3) δ

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Methyl substitution at para-, ortho-, and meta-position (7-9) was tolerated. Naphthyl derivative (10), five-and six-membered rings (11,21), and propylbenzenes were competent substrates (12,13). Halogenated substrates (14-17) gave moderate to low TTNs (215-1000), consistent with the trend of electron-rich substrates performing better than electron-poor ones.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Methyl substitution at para-, ortho-, and meta-position (7-9) was tolerated. Naphthyl derivative (10), five-and six-membered rings (11,21), and propylbenzenes were competent substrates (12,13). Halogenated substrates (14-17) gave moderate to low TTNs (215-1000), consistent with the trend of electron-rich substrates performing better than electron-poor ones.…”
Section: Methodssupporting
confidence: 62%
“…[6][7][8] In the presence of an appropriate organometallic catalyst (typically Rh, Ru, Ir, or Co), the resulting acyl(metal)nitrenoid species can undergo enantioselective CÀH insertion reactions to form amides. [9] This strategy has largely been confined to intramolecular lactam formation [10][11][12][13][14][15][16] and some cases of C(sp 2 )-H functionalization. [17,18] Only three enantioselective, intermolecular versions have been reported for C(sp 3 )-H amidation.…”
mentioning
confidence: 99%
“…Inspired by the success of bis(oxazoline) ligands in achieving regioselective intramolecular C-H insertion and asymmetric aziridination reactions, efforts towards designing a BOX catalyst for intramolecular asymmetric propargylic C-H insertion were undertaken. 39 A brief survey of ligands revealed that aryl-box ligands gave moderate ee for propargylic C-H bond amidation. Electronic modifications to these scaffolds and attempts to utilize NCIs to improve ee Scheme 12 Late-stage functionalization utilizing Ag-catalyzed NT.…”
Section: Asymmetric C-h Insertion Catalyzed By Silvermentioning
confidence: 99%
“…However, propargylic C-H amination has received relatively little attention (Scheme 1). Though several examples of intramolecular C-H amination of alkynes using metal nitrenoids have been reported, [24][25][26][27][28][29][30][31] the need for an appropriately tethered nucleophile fundamentally limits their substrate scope and generality. In contrast, intermolecular propargylic C-H aminations are surprisingly rare.…”
Section: Introductionmentioning
confidence: 99%